Factors Influencing Scabies Infection at the Al-Amin Islamic Boarding School in Sukabumi - Adinata, Thariq Mahathir; Sulistiyaningrum, Sri Katon; Saenong, Rizqa Haerani; Marindawati, Mieke (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2023)
Background: Scabies are a common health problem in many countries, mainly in densely populated areas. The prevalence of scabies in first community health services in Indonesia is 5.6-12.9%. Scabies infection is associated with a lack of health education, small bedrooms with too many people living in poor sanitation, and a crowded environment found in public Islamic boarding schools in Indonesia. Purposes: To investigate the correlation between characteristics, knowledge, and hygiene behavior with the incidence of scabies among boarding school students. Methods: This is a cross-sectional analytic study; 150 subjects were conducted in this study, and eight subjects were excluded. Subjects were conducted for an examination and filled out a questionnaire to diagnose the scabies infection. Bivariate and multivariate logistic regression analyses were used to assess the risk factors of subjects associated with scabies infection. Results: 142 subjects were analyzed, and 77 (54.2%) were diagnosed with scabies. From bivariate analyses, we found that gender (p0.0001), level of education (p0.0001), and clean behavior (p0.0001) were associated with scabies outcome. Male (p=0.015, OR 95% CI 4.3 (1.3 – 14.3), higher level of education (p=0.012, OR 95% CI 8 (1.58 – 41.2), and poor hygiene behavior (p0.0001, OR 95% CI 1 (1.02 – 1.09) were independently associated with scabies infection. Conclusions: There was a significant association between gender, level of education, and clean behavior with scabies outcome. Males, low levels of education, and poor hygiene behavior increase the incidence of scabies infection. Age, nutritional status, and knowledge of scabies were not associated with scabies outcome.